Protocolo de seguridad y salud en el trabajo en la georreferenciación de sistemas de suministros de energía eléctrica (2021)
This preliminary project intends to define the safe work procedure that all personnel involved in the execution of georeferencing processes of electrical energy supplies must comply with, this will serve as the basis for the implementation and evaluation of occupational risk, safety and health programs in the work according to the performance of this activity that will serve as a guide for companies interested in ensuring well-being and guaranteeing the necessary conditions for the adequate development of the work of the personnel involved The document contains the problem statement, the objectives, the methodology , scope and expected results.